A conversation ..., a contact : a collection of flash-fictions, auto-fictions, hybrid tales, letters, dream casting, dramatic sketches, semi-short fictions, prosaic experiments, chain-fictions - Mwanaka, Tendai R. (Chitungwiza, Zimbabwe : Mwanaka Media and Publishing Pvt Ltd, 2018)
A Conversation ..., A Contact has 22 fiction pieces around themes to do with political struggle, love relationships, heartbreaks and the resulting breakdowns, dreams, folklores, life, spirituality, anger, hate, grief, and all sorts of other human breaths.
Print version record.
JSTOR
Keywords: Zimbabwean fiction (English) -- 21st century; Roman zimbabwéen (anglais) -- 21e siècle.; prose (form); Zimbabwe; LITERARY COLLECTIONS / African; Zimbabwean fiction (English); 2000-2099